Maggie and the flying pigs - Baker, E. D. 1811-1861 (London : Bloomsbury, 2017)
"Maggie's newest chore at her friend Bob's stable is taking care of flying pigs--but they're not so easy to deal with! Maggie's used to putting up with a lot though, like her step-mother Zelia, who is trying to get Maggie's step-brother Peter a job at the stable. Peter working with Maggie? Yeah, right! Maybe when pigs fly ..."-- Provided by publisher
Primary
Fiction
Keywords: Magic -- Fiction; Stepbrothers -- Fiction; Swine -- Fiction; Animals, mythical -- Fiction; Fantasy -- Fiction; Stables -- Fiction